Call Me Maybe: Using Incentives and Follow-Ups to Increase Principals' Survey Response Rates. Issue 4 (1st October 2020) - Neal, Zachary; Neal, Jennifer Watling; Piteo, Amelia
Abstract: Educational researchers regularly collect survey data from educators, but struggle to encourage survey completion in this busy population, particularly when surveys are web-based. In this study we experimentally investigated the usefulness of follow-up phone calls and increased monetary incentives to non-respondents as strategies to boost response rates. We randomly assigned 540 hard-to-reach Michigan secondary school principals to one of four conditions (control, call, incentive, or call and incentive). We find that follow-up calls more than double the likelihood of survey completion, while the offer of a larger monetary incentive has no statistically significant effect. Integrating this finding with recent literature on survey response rates in educational settings, we conclude with a series of recommendations for researchers surveying principals and other school administrators.